2007
DOI: 10.1016/j.jcp.2007.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of Li-ion conduction in poly(ethylene oxide)

Abstract: Polyethylene oxide (PEO) containing a lithium salt (e.g. LiI) serves as a solid polymer electrolyte (SPE) in thin-film batteries and its ionic conductivity is a key parameter of their performance. We model and simulate Li + ion conduction in a single PEO molecule.Our simplified stochastic model of ionic motion is based on an analogy between protein channels of biological membranes that conduct Na + , K + , and other ions, and the PEO helical chain that conducts Li + ions. In contrast with protein channels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…In, 70,71 interchain ion hopping (between different molecular chains or segments) of PE has been expressed in terms of grain-boundary conductivity ( ⊥ σ GB ), and intrachain ion transport as bulk conductivity ( ⊥ σ Bulk ), both calculated from the Nyquist plot. It was found that ⊥ σ GB in the normal direction is lower by about a factor of five for the stretched PE as compared to the as-cast film.…”
Section: Polymer Systems With Decoupled Ion Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…In, 70,71 interchain ion hopping (between different molecular chains or segments) of PE has been expressed in terms of grain-boundary conductivity ( ⊥ σ GB ), and intrachain ion transport as bulk conductivity ( ⊥ σ Bulk ), both calculated from the Nyquist plot. It was found that ⊥ σ GB in the normal direction is lower by about a factor of five for the stretched PE as compared to the as-cast film.…”
Section: Polymer Systems With Decoupled Ion Transportmentioning
confidence: 99%
“…The more crystalline the cast PE, the more pronounced is the enhancement of its longitudinal conductivity. It was suggested 70 that there are at least three degrees of stretching-induced structural long-and short-range order, which include longitudinal alignment As-cast of spherulites, fibers composed of several polymer macromolecules and individual PEO helices. Lower ⊥ σ AC values of the stretched PE can be explained by the stiffening of the polymer chains followed by depression of host relaxation and ion transport associated with hopping between chains.…”
Section: 91mentioning
confidence: 99%
“…In [1] and [2] we developed a model of lithium ion conduction in dilute and concentrated polymer electrolytes (LiI : P (EO) n (3 ≤ n ≤ 100)), based on an analogy between protein channels of biological membranes that conduct N a + , K + , and other ions [6], and the PEO helical chain that conducts Li + ions. There are, however, significant differences between them: while protein channels are embedded in the cell membrane and their nearly rectilinear pores are aligned, the PEO molecules contain loops and their directions are random (see Figure 1.1).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we refine our molecular model of lithium ion conduction in dilute and concentrated polymer electrolytes (LiI : P (EO) n (3 ≤ n ≤ 100)) [1], by including additional geometrical features of the polymer molecule. The simplified stochastic model of ionic motion in [1] was based on an analogy between protein channels of biological membranes that conduct Na + , K + , and other ions, and the PEO helical chain that conducts Li + ions.…”
Section: Introductionmentioning
confidence: 99%
“…The simplified stochastic model of ionic motion in [1] was based on an analogy between protein channels of biological membranes that conduct Na + , K + , and other ions, and the PEO helical chain that conducts Li + ions. The main simplification in [1] was the linear model of the PEO molecule, which was only allowed to form a random angle with the direction of the external force field.…”
Section: Introductionmentioning
confidence: 99%